The State of the Muslim Ummah in Contemporary World - Babayo Sule (RIRAI Publisher, 2020)
The current state of affairs in the Muslim Ummah called for concern by every conscious Muslim contemporarily. The Islamic civilisation which introduced the whole world into the world of research and development, political organisation, economic prosperity and equality as well as cultural enrichment is now languishing in backwardness and crises. This study analysed the current condition of the Muslim Ummah in the present world based on the predicaments that are bedeviling the Islamic world. The problem is the nature and situation in which all the values and promises of Islamic civilisation are not utilised by the Muslims which threw them into their current comatose condition. The research used secondary sources of data such as the Quran, Hadith, books, journals and reports and statistics from organisations and agencies. The data collected were analysed critically using statistical and descriptive-analytical method to discuss some important themes of the subject matter. The work discovered that the current state of affairs of the Muslim Ummah is undesirable. It is dominated and encircled by internal crises, leadership failure, disunity, economic, political, social, cultural, military and technological backwardness in comparison with their Western counterparts. This has not been natural. The Decline of leadership in the Muslim world, Crusades and colonialism contributed to the predicaments of the Muslim world. The work suggested that the previous generation of Muslims faced trials and tribulations but they persevered and faced the challenges until God have mercy on them and rescue their situation. The same should be adopted by the present Ummah in dealing with its problems